On some new generalized difference statistically convergent sequence spaces defined by a sequence of orlicz functions - Bektaş, Ç.A.; Atıcı, G. (My University, 2010)
In this paper we introduce the new generalized difference sequence spaces l?(?nv , M, p, q, s), c(?nv , M, p, q, s), c0(?nv , M, p, q, s), m(?nv , M, p, q, s) and m0(?nv , M, p, q, s) defined over a seminormed sequence space (X, q). We study some of its properties, like completeness, solidity, symmetricity etc. We obtain some relations between these spaces as well as prove some inclusion result.
Keywords: Difference sequence spaces; Seminorm; Statistical convergence